Role of blood alcohol level on the risk and severity of trauma recurrence - Steven Char; Bharti Sharma; Monique Arnold; George Agriantonis; Jennifer Whittington; Navin Bhatia (Trauma Surgery & Acute Care Open)
Background Alcohol intoxication at the time of index trauma is associated with an increased risk of recurrent traumatic injury. It is unclear, however, whether the degree of intoxication impacts the risk of recurrence or its severity. This study aimed to analyze the relationship between alcohol level at index trauma and risk of recurrent trauma. We hypothesized that increasing levels of alcohol would be associated with an increased risk of trauma recurrence and severity.Methods We conducted a retrospective cohort study of adults who presented to our Level 1 trauma center between January 2020 and December 2022 with traumatic injury and a positive alcohol level (blood alcohol content (BAC)). The primary outcome of interest was recurrent trauma within 12 months. Secondary outcomes included injury severity score, hospital length of stay, and discharge location. We performed univariable and multivariable logistic regression with class balancing sensitivities controlling for baseline patient characteristics to analyze the association between risk factors and trauma recurrence.Results Of the 1,653 trauma encounters across 1,585 patients included in this study, 63 patients (3.8%) experienced re-injury within 12 months. Mean BAC at index trauma was higher among the recurrently injured compared with non-recurrently injured patients (270.0 mg/dL vs 221.0 mg/dL, p<0.001). Multivariate analysis revealed that for all-comers increasing BAC was weakly associated with an increased risk of trauma recurrence (OR 1.004, 95% CI: 1.001 to 1.007, p=0.013), but that among the highest tertile of intoxicated patients, increasing BAC was strongly associated with recurrence (OR 2.607, 95% CI: 1.166 to 6.448, p=0.026). Recurrently injured patients were more likely to have at least one medical comorbidity.Conclusions We found a differential effect of alcohol intoxication on the risk of trauma recurrence whereby increasing BAC was strongly associated with an increased risk of recurrence only among the most intoxicated patients.Level of Evidence III, Prognostic and epidemiological